Optimal placement criteria of hybrid mounting system for chassis in future mobility based on beam-type continuous smart structures - Yang Qiu; Dongwoo Hong; Byeongil Kim (Scientific Reports, 2023)
Abstract Recently, research into the development of hybrid and electric vehicles has been vigorously undertaken, indicating a trend toward the replacement of internal combustion engine vehicles. However, while high efficiency and light weight are crucial in the development of vehicles, they increase the excitation force of the engine. In addition, sensor placement in future mobility is very important since it causes malfunctioning of autonomous driving systems when the location and orientation of sensors are changed due to excessive vehicle vibration. To reduce the structure-borne noise and vibration caused by engine excitation, an active engine mounting system must be installed in an optimal location. Thus, in this study, to determine the optimal location for an active engine mounting system applied to a beam structure, a series of simulations with two different methodologies are performed. The overall beam structure with two active mounting systems is modeled based on the lumped parameter model. To determine the optimal position of the active mounting system, it is moved to equal intervals, and the force and phase of the active mounts at each location combination are calculated based on static and dynamic methods. The optimal position is suggested such that the vibration reduction is maximized, while the applied force is minimized. Additionally, a feasibility experiment is conducted to validate the proposed criteria and confirm the simulation results. The results demonstrate that the optimal location of the active engine mounting system with a minimized force requirement and maximized vibration reduction can be identified.